RETRACTED: Voyant tools as an analysis instrument of Pierre-louis le Roy’s text - Shvetsova Tatiana; Dulova Svetlana; Shakhova Veronika (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001